Hygric Properties of Lime-cement Plasters with the Addition of a Pozzolana. (2016) - Čáchová, Monika; Koťátková, Jaroslava; Koňáková, Dana; Vejmelková, Eva; Bartoňková, Eva; Černý, Robert
Abstract: There are more than seven billion people currently living on the Earth and the demands of population are rising. Lime and cement are parts of most building materials, so their global consumption grows. Therefore, it is necessary to think both economically and ecologically, and search for a suitable alternatives and replacements. This study is aimed at an investigation of the influence of pozzolana as the third binder component on basic physical characteristics and hygric properties of lime-cement plasters. Results show that with the increasing amount of pozzolana in the mixture the open porosity goes down. This is accompanied by a liquid water absorption decrease. Also diffusion parameters are somehow worsened, as the water vapour diffusion resistance factor increases.